Bacteriology and pathological anatomy of pneumonias in monkeys - V. A. Kalashnikova; N. S. Rudenko (Ветеринария сегодня)
Data on the etiological structure of potential pneumonia agents in monkeys based on postmortem findings and subsequent bacteriological tests of lung tissues collected from the organ areas showing morphological changes are presented. In the period between 2019 and the first half of 2021, 377 animals died of pneumonia. The highest pneumonia-associated mortality was observed in newborn (0–8-day-old) and baby monkeys under the age of 1 month (161 animals). Polysegmental bronchopneumonia was detected in the dead monkeys in 94.4% of cases, croupous pneumonias accounted for 4.5%. Pneumonia was typically the only disease detected in baby monkeys. The microbial landscape in pneumonia affected monkeys was characterized by a broad diversity: 899 bacteria of different taxonomic groups were isolated from the lung tissues. Staphylococci (23.8%) prevailed among gram-positive bacteria, Escherichia coli (32.1%) – among gram-negative bacteria. Streptococcus pneumoniae made up 0.3%. Based on data from bacteriological tests, the proportion of pneumonias of undetermined etiology was 0.7%. Besides, bacterial associations, two- or three-component ones as a rule, were detected in the tests of lung tissue samples. The most frequent combinations of associative pathogens were the following: Escherichia coli + Proteus spp. (24.7%), Staphylococcus aureus + Escherichia coli (19.6%), Staphylococcus spp. + Enterococcus spp. + Escherichia coli (35.5%), Staphylococcus spp. + Escherichia coli + Proteus spp. (21.2%). Almost all the enterobacteria detected have a high associativity coefficient and occur mainly in the form of associations. The analysis of the study results showed that practically any microorganism alone or in combination can cause pneumonia in an animal with a weakened immunity; therefore, the effect of microbiota should not be underestimated. Also, significance of associative microbes in the development of pneumonia in captive monkeys is increasing.